Entrepreneurial passion on the success of SME’s in Plateau State, Nigeria: The role of entrepreneurial skills - Kusa, Nanfa Danjuma; Danladi, Nson Yilkes (Journal of Sustainable Tourism and Entrepreneurship, 2023)
Purpose: The purpose of the study was to examine the extent to which entrepreneurial skills mediate the influences of entrepreneurial passion on the entrepreneurial success of SMEs in Plateau State, Nigeria. Research Methodology:  The researchers self-administered 337 questionnaires to SME owners in the Jos North and South LGA of Plateau State, Nigeria, and obtained a response rate of 91.1%. Quantitative data were analyzed using PLS-SEM version 3.0. Results: Results showed that Entrepreneurial skills partially and fully mediated the influence of entrepreneurial passion on entrepreneurial success. Limitations: The study was limited to SME owners in the Jos North and South LGA of Plateau State, Nigeria. Contribution: This study contributes to the body of knowledge in entrepreneurship literature. It helps policymakers formulate holistic policies that will encourage entrepreneurship and skill acquisition, as well as enhance the socio-economic well-being of people via entrepreneurship. It also helps entrepreneurs, business owners, managers, and aspiring entrepreneurs learn and obtain the necessary skills, knowledge, and abilities to succeed.